A comparative simulation study of rate adaptation algorithms in wireless LANs. (11th September 2013) - Huang, Tingpei; Chen, Haiming; Cui, Li; Zhang, Zhaoliang
Wireless channel condition varies quickly and unpredictably, which is the main reason leading to the low performance of 802.11 wireless local area networks. One effective way to overcome the above problem is rate adaptation, which adaptively selects an appropriate transmission rate according to current channel conditions. A number of rate adaptation algorithms have been proposed in the literatures. However, few of them have been thoroughly evaluated by simulations. It is necessary to conduct a comparative study of these rate adaptation mechanisms, to have a comprehensive view about their impacts on the performance of applications in different channel conditions. In this paper, we perform an extensive comparative simulation study on several well–known rate adaptation algorithms based on ns–3. We quantify their performance for aggregate network throughput in the following two environments: collision–concerned and mobility–concerned. This work is an important step to understand the behaviour of different rate adaptation algorithms.